src/HOL/Hyperreal/NthRoot.thy
 author huffman Mon, 14 May 2007 09:27:24 +0200 changeset 22961 e499ded5d0fc parent 22956 617140080e6a child 22968 7134874437ac permissions -rw-r--r--
remove redundant lemmas
```
(*  Title       : NthRoot.thy
Author      : Jacques D. Fleuriot
Copyright   : 1998  University of Cambridge
Conversion to Isar and new proofs by Lawrence C Paulson, 2004
*)

header {* Nth Roots of Real Numbers *}

theory NthRoot
imports SEQ Parity
begin

subsection {* Existence of Nth Root *}

text {*
Various lemmas needed for this result. We follow the proof given by
John Lindsay Orr (\texttt{jorr@math.unl.edu}) in his Analysis
Webnotes available at \url{http://www.math.unl.edu/~webnotes}.

Lemmas about sequences of reals are used to reach the result.
*}

lemma lemma_nth_realpow_non_empty:
"[| (0::real) < a; 0 < n |] ==> \<exists>s. s : {x. x ^ n <= a & 0 < x}"
apply (case_tac "1 <= a")
apply (rule_tac x = 1 in exI)
apply (drule_tac [2] linorder_not_le [THEN iffD1])
apply (drule_tac [2] less_not_refl2 [THEN not0_implies_Suc], simp)
apply (force intro!: realpow_Suc_le_self simp del: realpow_Suc)
done

text{*Used only just below*}
lemma realpow_ge_self2: "[| (1::real) \<le> r; 0 < n |] ==> r \<le> r ^ n"
by (insert power_increasing [of 1 n r], simp)

lemma lemma_nth_realpow_isUb_ex:
"[| (0::real) < a; 0 < n |]
==> \<exists>u. isUb (UNIV::real set) {x. x ^ n <= a & 0 < x} u"
apply (case_tac "1 <= a")
apply (rule_tac x = a in exI)
apply (drule_tac [2] linorder_not_le [THEN iffD1])
apply (rule_tac [2] x = 1 in exI)
apply (rule_tac [!] setleI [THEN isUbI], safe)
apply (simp_all (no_asm))
apply (rule_tac [!] ccontr)
apply (drule_tac [!] linorder_not_le [THEN iffD1])
apply (drule realpow_ge_self2, assumption)
apply (drule_tac n = n in realpow_less)
apply (assumption+)
apply (drule real_le_trans, assumption)
apply (drule_tac y = "y ^ n" in order_less_le_trans, assumption, simp)
apply (drule_tac n = n in zero_less_one [THEN realpow_less], auto)
done

lemma nth_realpow_isLub_ex:
"[| (0::real) < a; 0 < n |]
==> \<exists>u. isLub (UNIV::real set) {x. x ^ n <= a & 0 < x} u"
by (blast intro: lemma_nth_realpow_isUb_ex lemma_nth_realpow_non_empty reals_complete)

subsubsection {* First Half -- Lemmas First *}

lemma lemma_nth_realpow_seq:
"isLub (UNIV::real set) {x. x ^ n <= a & (0::real) < x} u
==> u + inverse(real (Suc k)) ~: {x. x ^ n <= a & 0 < x}"
apply (safe, drule isLubD2, blast)
apply (simp add: linorder_not_less [symmetric])
done

lemma lemma_nth_realpow_isLub_gt_zero:
"[| isLub (UNIV::real set) {x. x ^ n <= a & (0::real) < x} u;
0 < a; 0 < n |] ==> 0 < u"
apply (drule lemma_nth_realpow_non_empty, auto)
apply (drule_tac y = s in isLub_isUb [THEN isUbD])
apply (auto intro: order_less_le_trans)
done

lemma lemma_nth_realpow_isLub_ge:
"[| isLub (UNIV::real set) {x. x ^ n <= a & (0::real) < x} u;
0 < a; 0 < n |] ==> ALL k. a <= (u + inverse(real (Suc k))) ^ n"
apply safe
apply (frule lemma_nth_realpow_seq, safe)
apply (auto elim: order_less_asym simp add: linorder_not_less [symmetric]
iff: real_0_less_add_iff) --{*legacy iff rule!*}
apply (simp add: linorder_not_less)
apply (rule order_less_trans [of _ 0])
apply (auto intro: lemma_nth_realpow_isLub_gt_zero)
done

text{*First result we want*}
lemma realpow_nth_ge:
"[| (0::real) < a; 0 < n;
isLub (UNIV::real set)
{x. x ^ n <= a & 0 < x} u |] ==> a <= u ^ n"
apply (frule lemma_nth_realpow_isLub_ge, safe)
apply (rule LIMSEQ_inverse_real_of_nat_add [THEN LIMSEQ_pow, THEN LIMSEQ_le_const])
apply (auto simp add: real_of_nat_def)
done

subsubsection {* Second Half *}

lemma less_isLub_not_isUb:
"[| isLub (UNIV::real set) S u; x < u |]
==> ~ isUb (UNIV::real set) S x"
apply safe
apply (drule isLub_le_isUb, assumption)
apply (drule order_less_le_trans, auto)
done

lemma not_isUb_less_ex:
"~ isUb (UNIV::real set) S u ==> \<exists>x \<in> S. u < x"
apply (rule ccontr, erule contrapos_np)
apply (rule setleI [THEN isUbI])
apply (auto simp add: linorder_not_less [symmetric])
done

lemma real_mult_less_self: "0 < r ==> r * (1 + -inverse(real (Suc n))) < r"
apply (simp (no_asm) add: right_distrib)
apply (rule add_less_cancel_left [of "-r", THEN iffD1])
apply (auto intro: mult_pos_pos
simp add: add_assoc [symmetric] neg_less_0_iff_less)
done

lemma real_of_nat_inverse_le_iff:
"(inverse (real(Suc n)) \<le> r) = (1 \<le> r * real(Suc n))"
by (simp add: inverse_eq_divide pos_divide_le_eq)

lemma real_mult_add_one_minus_ge_zero:
"0 < r ==>  0 <= r*(1 + -inverse(real (Suc n)))"
by (simp add: zero_le_mult_iff real_of_nat_inverse_le_iff real_0_le_add_iff)

lemma lemma_nth_realpow_isLub_le:
"[| isLub (UNIV::real set) {x. x ^ n <= a & (0::real) < x} u;
0 < a; 0 < n |] ==> ALL k. (u*(1 + -inverse(real (Suc k)))) ^ n <= a"
apply safe
apply (frule less_isLub_not_isUb [THEN not_isUb_less_ex])
apply (rule_tac n = k in real_mult_less_self)
apply (blast intro: lemma_nth_realpow_isLub_gt_zero, safe)
apply (drule_tac n = k in
lemma_nth_realpow_isLub_gt_zero [THEN real_mult_add_one_minus_ge_zero], assumption+)
apply (blast intro: order_trans order_less_imp_le power_mono)
done

text{*Second result we want*}
lemma realpow_nth_le:
"[| (0::real) < a; 0 < n;
isLub (UNIV::real set)
{x. x ^ n <= a & 0 < x} u |] ==> u ^ n <= a"
apply (frule lemma_nth_realpow_isLub_le, safe)
apply (rule LIMSEQ_inverse_real_of_nat_add_minus_mult
[THEN LIMSEQ_pow, THEN LIMSEQ_le_const2])
apply (auto simp add: real_of_nat_def)
done

text{*The theorem at last!*}
lemma realpow_nth: "[| (0::real) < a; 0 < n |] ==> \<exists>r. r ^ n = a"
apply (frule nth_realpow_isLub_ex, auto)
apply (auto intro: realpow_nth_le realpow_nth_ge order_antisym)
done

text {* positive only *}
lemma realpow_pos_nth: "[| (0::real) < a; 0 < n |] ==> \<exists>r. 0 < r & r ^ n = a"
apply (frule nth_realpow_isLub_ex, auto)
apply (auto intro: realpow_nth_le realpow_nth_ge order_antisym lemma_nth_realpow_isLub_gt_zero)
done

lemma realpow_pos_nth2: "(0::real) < a  ==> \<exists>r. 0 < r & r ^ Suc n = a"
by (blast intro: realpow_pos_nth)

text {* uniqueness of nth positive root *}
lemma realpow_pos_nth_unique:
"[| (0::real) < a; 0 < n |] ==> EX! r. 0 < r & r ^ n = a"
apply (auto intro!: realpow_pos_nth)
apply (cut_tac x = r and y = y in linorder_less_linear, auto)
apply (drule_tac x = r in realpow_less)
apply (drule_tac [4] x = y in realpow_less, auto)
done

subsection {* Nth Root *}

text {* We define roots of negative reals such that
@{term "root n (- x) = - root n x"}. This allows
us to omit side conditions from many theorems. *}

definition
root :: "[nat, real] \<Rightarrow> real" where
"root n x = (if 0 < x then (THE u. 0 < u \<and> u ^ n = x) else
if x < 0 then - (THE u. 0 < u \<and> u ^ n = - x) else 0)"

lemma real_root_zero [simp]: "root n 0 = 0"
unfolding root_def by simp

lemma real_root_minus: "0 < n \<Longrightarrow> root n (- x) = - root n x"
unfolding root_def by simp

lemma real_root_gt_zero: "\<lbrakk>0 < n; 0 < x\<rbrakk> \<Longrightarrow> 0 < root n x"
apply (simp add: root_def)
apply (drule (1) realpow_pos_nth_unique)
apply (erule theI' [THEN conjunct1])
done

lemma real_root_pow_pos: (* TODO: rename *)
"\<lbrakk>0 < n; 0 < x\<rbrakk> \<Longrightarrow> root n x ^ n = x"
apply (simp add: root_def)
apply (drule (1) realpow_pos_nth_unique)
apply (erule theI' [THEN conjunct2])
done

lemma real_root_pow_pos2 [simp]: (* TODO: rename *)
"\<lbrakk>0 < n; 0 \<le> x\<rbrakk> \<Longrightarrow> root n x ^ n = x"
by (auto simp add: order_le_less real_root_pow_pos)

lemma real_root_ge_zero: "\<lbrakk>0 < n; 0 \<le> x\<rbrakk> \<Longrightarrow> 0 \<le> root n x"
by (auto simp add: order_le_less real_root_gt_zero)

lemma real_root_power_cancel: "\<lbrakk>0 < n; 0 \<le> x\<rbrakk> \<Longrightarrow> root n (x ^ n) = x"
apply (subgoal_tac "0 \<le> x ^ n")
apply (subgoal_tac "0 \<le> root n (x ^ n)")
apply (subgoal_tac "root n (x ^ n) ^ n = x ^ n")
apply (erule (3) power_eq_imp_eq_base)
apply (erule (1) real_root_pow_pos2)
apply (erule (1) real_root_ge_zero)
apply (erule zero_le_power)
done

lemma real_root_pos_unique:
"\<lbrakk>0 < n; 0 \<le> y; y ^ n = x\<rbrakk> \<Longrightarrow> root n x = y"
by (erule subst, rule real_root_power_cancel)

lemma real_root_one [simp]: "0 < n \<Longrightarrow> root n 1 = 1"
by (simp add: real_root_pos_unique)

text {* Root function is strictly monotonic, hence injective *}

lemma real_root_less_mono_lemma:
"\<lbrakk>0 < n; 0 \<le> x; x < y\<rbrakk> \<Longrightarrow> root n x < root n y"
apply (subgoal_tac "0 \<le> y")
apply (subgoal_tac "root n x ^ n < root n y ^ n")
apply (erule power_less_imp_less_base)
apply (erule (1) real_root_ge_zero)
apply simp
apply simp
done

lemma real_root_less_mono: "\<lbrakk>0 < n; x < y\<rbrakk> \<Longrightarrow> root n x < root n y"
apply (cases "0 \<le> x")
apply (erule (2) real_root_less_mono_lemma)
apply (cases "0 \<le> y")
apply (rule_tac y=0 in order_less_le_trans)
apply (subgoal_tac "0 < root n (- x)")
apply (simp add: real_root_minus)
apply (simp add: real_root_gt_zero)
apply (simp add: real_root_ge_zero)
apply (subgoal_tac "root n (- y) < root n (- x)")
apply (simp add: real_root_minus)
apply (simp add: real_root_less_mono_lemma)
done

lemma real_root_le_mono: "\<lbrakk>0 < n; x \<le> y\<rbrakk> \<Longrightarrow> root n x \<le> root n y"
by (auto simp add: order_le_less real_root_less_mono)

lemma real_root_less_iff [simp]:
"0 < n \<Longrightarrow> (root n x < root n y) = (x < y)"
apply (cases "x < y")
apply (simp add: real_root_less_mono)
apply (simp add: linorder_not_less real_root_le_mono)
done

lemma real_root_le_iff [simp]:
"0 < n \<Longrightarrow> (root n x \<le> root n y) = (x \<le> y)"
apply (cases "x \<le> y")
apply (simp add: real_root_le_mono)
apply (simp add: linorder_not_le real_root_less_mono)
done

lemma real_root_eq_iff [simp]:
"0 < n \<Longrightarrow> (root n x = root n y) = (x = y)"
by (simp add: order_eq_iff)

lemmas real_root_gt_0_iff [simp] = real_root_less_iff [where x=0, simplified]
lemmas real_root_lt_0_iff [simp] = real_root_less_iff [where y=0, simplified]
lemmas real_root_ge_0_iff [simp] = real_root_le_iff [where x=0, simplified]
lemmas real_root_le_0_iff [simp] = real_root_le_iff [where y=0, simplified]
lemmas real_root_eq_0_iff [simp] = real_root_eq_iff [where y=0, simplified]

text {* Roots of multiplication and division *}

lemma real_root_mult_lemma:
"\<lbrakk>0 < n; 0 \<le> x; 0 \<le> y\<rbrakk> \<Longrightarrow> root n (x * y) = root n x * root n y"
by (simp add: real_root_pos_unique mult_nonneg_nonneg power_mult_distrib)

lemma real_root_inverse_lemma:
"\<lbrakk>0 < n; 0 \<le> x\<rbrakk> \<Longrightarrow> root n (inverse x) = inverse (root n x)"
by (simp add: real_root_pos_unique power_inverse [symmetric])

lemma real_root_mult:
assumes n: "0 < n"
shows "root n (x * y) = root n x * root n y"
proof (rule linorder_le_cases, rule_tac [!] linorder_le_cases)
assume "0 \<le> x" and "0 \<le> y"
thus ?thesis by (rule real_root_mult_lemma [OF n])
next
assume "0 \<le> x" and "y \<le> 0"
hence "0 \<le> x" and "0 \<le> - y" by simp_all
hence "root n (x * - y) = root n x * root n (- y)"
by (rule real_root_mult_lemma [OF n])
thus ?thesis by (simp add: real_root_minus [OF n])
next
assume "x \<le> 0" and "0 \<le> y"
hence "0 \<le> - x" and "0 \<le> y" by simp_all
hence "root n (- x * y) = root n (- x) * root n y"
by (rule real_root_mult_lemma [OF n])
thus ?thesis by (simp add: real_root_minus [OF n])
next
assume "x \<le> 0" and "y \<le> 0"
hence "0 \<le> - x" and "0 \<le> - y" by simp_all
hence "root n (- x * - y) = root n (- x) * root n (- y)"
by (rule real_root_mult_lemma [OF n])
thus ?thesis by (simp add: real_root_minus [OF n])
qed

lemma real_root_inverse:
assumes n: "0 < n"
shows "root n (inverse x) = inverse (root n x)"
proof (rule linorder_le_cases)
assume "0 \<le> x"
thus ?thesis by (rule real_root_inverse_lemma [OF n])
next
assume "x \<le> 0"
hence "0 \<le> - x" by simp
hence "root n (inverse (- x)) = inverse (root n (- x))"
by (rule real_root_inverse_lemma [OF n])
thus ?thesis by (simp add: real_root_minus [OF n])
qed

lemma real_root_divide:
"0 < n \<Longrightarrow> root n (x / y) = root n x / root n y"
by (simp add: divide_inverse real_root_mult real_root_inverse)

lemma real_root_power:
"0 < n \<Longrightarrow> root n (x ^ k) = root n x ^ k"
by (induct k, simp_all add: real_root_mult)

subsection {* Square Root *}

definition
sqrt :: "real \<Rightarrow> real" where
"sqrt = root 2"

lemma pos2: "0 < (2::nat)" by simp

lemma real_sqrt_unique: "\<lbrakk>y\<twosuperior> = x; 0 \<le> y\<rbrakk> \<Longrightarrow> sqrt x = y"
unfolding sqrt_def by (rule real_root_pos_unique [OF pos2])

lemma real_sqrt_abs [simp]: "sqrt (x\<twosuperior>) = \<bar>x\<bar>"
apply (rule real_sqrt_unique)
apply (rule power2_abs)
apply (rule abs_ge_zero)
done

lemma real_sqrt_pow2 [simp]: "0 \<le> x \<Longrightarrow> (sqrt x)\<twosuperior> = x"
unfolding sqrt_def by (rule real_root_pow_pos2 [OF pos2])

lemma real_sqrt_pow2_iff [simp]: "((sqrt x)\<twosuperior> = x) = (0 \<le> x)"
apply (rule iffI)
apply (erule subst)
apply (rule zero_le_power2)
apply (erule real_sqrt_pow2)
done

lemma real_sqrt_zero [simp]: "sqrt 0 = 0"
unfolding sqrt_def by (rule real_root_zero)

lemma real_sqrt_one [simp]: "sqrt 1 = 1"
unfolding sqrt_def by (rule real_root_one [OF pos2])

lemma real_sqrt_minus: "sqrt (- x) = - sqrt x"
unfolding sqrt_def by (rule real_root_minus [OF pos2])

lemma real_sqrt_mult: "sqrt (x * y) = sqrt x * sqrt y"
unfolding sqrt_def by (rule real_root_mult [OF pos2])

lemma real_sqrt_inverse: "sqrt (inverse x) = inverse (sqrt x)"
unfolding sqrt_def by (rule real_root_inverse [OF pos2])

lemma real_sqrt_divide: "sqrt (x / y) = sqrt x / sqrt y"
unfolding sqrt_def by (rule real_root_divide [OF pos2])

lemma real_sqrt_power: "sqrt (x ^ k) = sqrt x ^ k"
unfolding sqrt_def by (rule real_root_power [OF pos2])

lemma real_sqrt_gt_zero: "0 < x \<Longrightarrow> 0 < sqrt x"
unfolding sqrt_def by (rule real_root_gt_zero [OF pos2])

lemma real_sqrt_ge_zero: "0 \<le> x \<Longrightarrow> 0 \<le> sqrt x"
unfolding sqrt_def by (rule real_root_ge_zero [OF pos2])

lemma real_sqrt_less_mono: "x < y \<Longrightarrow> sqrt x < sqrt y"
unfolding sqrt_def by (rule real_root_less_mono [OF pos2])

lemma real_sqrt_le_mono: "x \<le> y \<Longrightarrow> sqrt x \<le> sqrt y"
unfolding sqrt_def by (rule real_root_le_mono [OF pos2])

lemma real_sqrt_less_iff [simp]: "(sqrt x < sqrt y) = (x < y)"
unfolding sqrt_def by (rule real_root_less_iff [OF pos2])

lemma real_sqrt_le_iff [simp]: "(sqrt x \<le> sqrt y) = (x \<le> y)"
unfolding sqrt_def by (rule real_root_le_iff [OF pos2])

lemma real_sqrt_eq_iff [simp]: "(sqrt x = sqrt y) = (x = y)"
unfolding sqrt_def by (rule real_root_eq_iff [OF pos2])

lemmas real_sqrt_gt_0_iff [simp] = real_sqrt_less_iff [where x=0, simplified]
lemmas real_sqrt_lt_0_iff [simp] = real_sqrt_less_iff [where y=0, simplified]
lemmas real_sqrt_ge_0_iff [simp] = real_sqrt_le_iff [where x=0, simplified]
lemmas real_sqrt_le_0_iff [simp] = real_sqrt_le_iff [where y=0, simplified]
lemmas real_sqrt_eq_0_iff [simp] = real_sqrt_eq_iff [where y=0, simplified]

lemmas real_sqrt_gt_1_iff [simp] = real_sqrt_less_iff [where x=1, simplified]
lemmas real_sqrt_lt_1_iff [simp] = real_sqrt_less_iff [where y=1, simplified]
lemmas real_sqrt_ge_1_iff [simp] = real_sqrt_le_iff [where x=1, simplified]
lemmas real_sqrt_le_1_iff [simp] = real_sqrt_le_iff [where y=1, simplified]
lemmas real_sqrt_eq_1_iff [simp] = real_sqrt_eq_iff [where y=1, simplified]

lemma not_real_square_gt_zero [simp]: "(~ (0::real) < x*x) = (x = 0)"
apply auto
apply (cut_tac x = x and y = 0 in linorder_less_linear)
apply (simp add: zero_less_mult_iff)
done

lemma real_sqrt_abs2 [simp]: "sqrt(x*x) = \<bar>x\<bar>"
apply (subst power2_eq_square [symmetric])
apply (rule real_sqrt_abs)
done

lemma real_sqrt_pow2_gt_zero: "0 < x ==> 0 < (sqrt x)\<twosuperior>"
by simp (* TODO: delete *)

lemma real_sqrt_not_eq_zero: "0 < x ==> sqrt x \<noteq> 0"
by simp (* TODO: delete *)

lemma real_inv_sqrt_pow2: "0 < x ==> inverse (sqrt(x)) ^ 2 = inverse x"
by (simp add: power_inverse [symmetric])

lemma real_sqrt_eq_zero_cancel: "[| 0 \<le> x; sqrt(x) = 0|] ==> x = 0"
by simp

lemma real_sqrt_ge_one: "1 \<le> x ==> 1 \<le> sqrt x"
by simp

lemma sqrt_divide_self_eq:
assumes nneg: "0 \<le> x"
shows "sqrt x / x = inverse (sqrt x)"
proof cases
assume "x=0" thus ?thesis by simp
next
assume nz: "x\<noteq>0"
hence pos: "0<x" using nneg by arith
show ?thesis
proof (rule right_inverse_eq [THEN iffD1, THEN sym])
show "sqrt x / x \<noteq> 0" by (simp add: divide_inverse nneg nz)
show "inverse (sqrt x) / (sqrt x / x) = 1"
by (simp add: divide_inverse mult_assoc [symmetric]
power2_eq_square [symmetric] real_inv_sqrt_pow2 pos nz)
qed
qed

lemma real_divide_square_eq [simp]: "(((r::real) * a) / (r * r)) = a / r"
apply (simp add: divide_inverse)
apply (case_tac "r=0")
apply (auto simp add: mult_ac)
done

subsection {* Square Root of Sum of Squares *}

lemma real_sqrt_mult_self_sum_ge_zero [simp]: "0 \<le> sqrt(x*x + y*y)"
by (rule real_sqrt_ge_zero [OF real_mult_self_sum_ge_zero])

lemma real_sqrt_sum_squares_ge_zero [simp]: "0 \<le> sqrt (x\<twosuperior> + y\<twosuperior>)"
by simp

lemma real_sqrt_sum_squares_mult_ge_zero [simp]:
"0 \<le> sqrt ((x\<twosuperior> + y\<twosuperior>)*(xa\<twosuperior> + ya\<twosuperior>))"
by (auto intro!: real_sqrt_ge_zero simp add: zero_le_mult_iff)

lemma real_sqrt_sum_squares_mult_squared_eq [simp]:
"sqrt ((x\<twosuperior> + y\<twosuperior>) * (xa\<twosuperior> + ya\<twosuperior>)) ^ 2 = (x\<twosuperior> + y\<twosuperior>) * (xa\<twosuperior> + ya\<twosuperior>)"
by (auto simp add: zero_le_mult_iff)

lemma real_sqrt_sum_squares_ge1 [simp]: "x \<le> sqrt(x\<twosuperior> + y\<twosuperior>)"
by (rule power2_le_imp_le, simp_all)

lemma real_sqrt_sum_squares_ge2 [simp]: "y \<le> sqrt(x\<twosuperior> + y\<twosuperior>)"
by (rule power2_le_imp_le, simp_all)

lemma power2_sum:
fixes x y :: "'a::{number_ring,recpower}"
shows "(x + y)\<twosuperior> = x\<twosuperior> + y\<twosuperior> + 2 * x * y"
by (simp add: left_distrib right_distrib power2_eq_square)

lemma power2_diff:
fixes x y :: "'a::{number_ring,recpower}"
shows "(x - y)\<twosuperior> = x\<twosuperior> + y\<twosuperior> - 2 * x * y"
by (simp add: left_diff_distrib right_diff_distrib power2_eq_square)

lemma real_sqrt_sum_squares_triangle_ineq:
"sqrt ((a + c)\<twosuperior> + (b + d)\<twosuperior>) \<le> sqrt (a\<twosuperior> + b\<twosuperior>) + sqrt (c\<twosuperior> + d\<twosuperior>)"
apply (rule power2_le_imp_le, simp)
apply (simp add: power2_sum)
apply (simp only: mult_assoc right_distrib [symmetric])
apply (rule mult_left_mono)
apply (rule power2_le_imp_le)
apply (simp add: power2_sum power_mult_distrib)
apply (simp add: ring_distrib)
apply (subgoal_tac "0 \<le> b\<twosuperior> * c\<twosuperior> + a\<twosuperior> * d\<twosuperior> - 2 * (a * c) * (b * d)", simp)
apply (rule_tac b="(a * d - b * c)\<twosuperior>" in ord_le_eq_trans)
apply (rule zero_le_power2)
apply (simp add: power2_diff power_mult_distrib)
apply (simp add: mult_nonneg_nonneg)
apply simp
apply (simp add: add_increasing)
done

text "Legacy theorem names:"
lemmas real_root_pos2 = real_root_power_cancel
lemmas real_root_pos_pos = real_root_gt_zero [THEN order_less_imp_le]
lemmas real_root_pos_pos_le = real_root_ge_zero
lemmas real_sqrt_mult_distrib = real_sqrt_mult
lemmas real_sqrt_mult_distrib2 = real_sqrt_mult
lemmas real_sqrt_eq_zero_cancel_iff = real_sqrt_eq_0_iff

(* needed for CauchysMeanTheorem.het_base from AFP *)
lemma real_root_pos: "0 < x \<Longrightarrow> root (Suc n) (x ^ (Suc n)) = x"
by (rule real_root_power_cancel [OF zero_less_Suc order_less_imp_le])

(* FIXME: the stronger version of real_root_less_iff
breaks CauchysMeanTheorem.list_gmean_gt_iff from AFP. *)

declare real_root_less_iff [simp del]
lemma real_root_less_iff_nonneg [simp]:
"\<lbrakk>0 < n; 0 \<le> x; 0 \<le> y\<rbrakk> \<Longrightarrow> (root n x < root n y) = (x < y)"
by (rule real_root_less_iff)

end
```